2015
DOI: 10.1111/bju.13162
|View full text |Cite
|
Sign up to set email alerts
|

Responder and health‐related quality of life analyses in men with lower urinary tract symptoms treated with a fixed‐dose combination of solifenacin and tamsulosin oral‐controlled absorption system: results from the NEPTUNE study

Abstract: Responder and health-related quality of life analyses in men with lower urinary tract symptoms treated with a fixed-dose combination of solifenacin and tamsulosin oral-controlled absorption system: results from the NEPTUNE study ObjectiveTo evaluate the effect of a fixed-dose combination (FDC) of solifenacin and an oral-controlled absorption system (OCAS TM ) formulation of tamsulosin (TOCAS) on healthrelated quality of life (HRQoL) in men with lower urinary tract symptoms associated with benign prostatic hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
(58 reference statements)
1
6
0
1
Order By: Relevance
“…Furthermore, treatment satisfaction and patient‐reported health status were also improved. These results are consistent with those observed in clinical trial settings that demonstrated improvements in clinical outcomes and HRQoL with Vesomni …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, treatment satisfaction and patient‐reported health status were also improved. These results are consistent with those observed in clinical trial settings that demonstrated improvements in clinical outcomes and HRQoL with Vesomni …”
Section: Discussionsupporting
confidence: 90%
“…Monotherapy with α‐blockers and 5‐ARIs are among the currently available medications that can improve HRQoL by relieving urinary symptoms; 5‐ARIs are also effective in reducing the risk of complications associated with BPH . However, since α‐blockers and 5‐ARIs predominantly improve voiding symptoms, add‐on therapy with an antimuscarinic is often required to relieve residual storage symptoms . The efficacy of α‐blockers in combination with antimuscarinics has been demonstrated in numerous clinical trials conducted in different countries, including some European countries .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[95][96][97][98] Two studies evaluated the fixed combination of tamsulosin 0.4 mg and solifenacin 6 and 9 mg versus tamsulosin alone and placebo in men with moderate-to-severe LUTS. 95,99 The results of these studies showed that the combination of solifenacin 6 mg and tamsulosin significantly improved storage and voiding symptoms, as well as QoL parameters, over placebo. In a 52-week extension of the initial studies, clinical efficacy was maintained while urinary retention occurred in only 1.1% of the patients, with only 0.7% of them requiring a permanent catheter.…”
Section: α1-blocker Plus Antimuscarinicmentioning
confidence: 99%
“…Основными препаратами для медикаментозного лечения ДГПЖ/СНМП являются альфа-1-адреноблокаторы, ингибиторы 5-альфа-редутазы, ингибиторы фосфодиэстеразы 5 типа и М-холиноблокаторы (по показаниям) [9][10][11].…”
unclassified